The emergence and growth of private credit as a financing option in corporate finance : The perspective of Finnish finance professionals - Käkelä, Mikke (My University, 2024)
This thesis provides an insightful look into private credit, which has emerged as an alternative financing option in corporate finance over the past few decades. Private credit is a broad term for a market that consists of non-bank lenders offering financing options to mainly non-listed companies, hence the term “private credit”. The emergence of private credit was heavily influenced by the 2008 financial crisis, which was caused by overly lenient lending of banks, especially in subprime mortgages. These events triggered a global banking and financial crisis, which caused major changes in the ways banks can operate and take risks. The changes in banking practices caused a deficit of available loan capital in the markets, especially for companies that fell under the new, stricter regulations of banks. Investment companies began to find ways to invest in the riskier companies that were unable to get funding from banks in search of higher profits. The private credit market is still a relatively new and developing market that offers intriguing opportunities for future prospects. Companies that are willing to invest in private credit deals must accept the higher-than-average risk of the companies that they are lending to, but in return will be rewarded with higher returns for their investments. For the empirical part of this thesis, a qualitative study was conducted by utilising expert interviews as the data collection method. The subjects interviewed for the study are Finnish professionals in corporate finance and have multiple years of relevant experience. The experts were selected from private credit and banking backgrounds to gain insight of the views from different perspectives. The study was conducted to find out the views of industry professionals on what they saw to be the defining characteristics and uses of private credit, how the experts viewed the emergence and growth of private credit as a whole and what they saw to be the advantages and disadvantages of private credit. The research also aimed to find out what the professionals saw to be the reasons behind the rapid growth of private credit as a financing option and how will the private credit market continue to grow in the future. As the phenomenon is relatively new and developing it was interesting to compare the views of the experts with existing literature to see how well real-life experience corresponds with current literature on the topic. The data analysis of the study was conducted as a thematic analysis based on the research question and sub-questions in relation to the existing literature. In the study the trends of private credit were evaluated both from a local perspective, as well as on the global scale. The emergence and growth of private credit is a global phenomenon, and the large-scale trends are applicable on a global scale, but it was also interesting to see how the changes apply to the local market in Finland. In the study it was found that the Finnish finance professionals saw plenty of potential in private credit and considered it to have an overall positive effect in the corporate finance market, as it allows companies to gain access to capital easier. As the riskier investments move away from banks to private credit investors, it should also make the global financial industry safer, by reducing the risk of future banking crises caused by extravagant risk taking. The experts saw plenty of potential for future growth of private credit as banking regulations continue to become stricter, thus opening more opportunities for private credit investments.
Keywords: Private Credit, Corporate Finance, Banking, Lending, Alternative Investments.